Sulforaphane alleviates hepatocyte pyroptosis via activating Nrf2-HO-1 signaling during septic acute liver injury - Xie, Shiying; Liu, Min; Chen, Lei; Xie, Yincai; Liu, Li; Chen, Weina; Huang, Huanwen (Frontiers in Pharmacology, 2025)
ObjectiveAcute liver injury (ALI) caused by sepsis is a fatal disease with a high mortality rate and poor prognosis. Sulforaphane (SFN) is a natural isothiocyanate that has robust antioxidant and anti-inflammatory properties. The aim of this study was to identify the pharmacological effects and therapeutic mechanisms of SFN in lipopolysaccharide (LPS)-induced ALI.MethodsThe role of SFN in ALI was investigated using a mouse model of LPS-induced ALI. Briefly, eighteen mice were divided into three groups: control, LPS, and LPS + SFN, which were intraperitoneally injected for 2 days before LPS treatment. 24 h after the LPS injection, blood and liver tissues were collected for further analysis.ResultsThe hematoxylin and eosin (HE) staining showed a lot of visible necrosis areas, inflammatory cell infiltration, and congestion in liver. Meanwhile, Ly6G and F4/80 staining showed increased infiltration of neutrophils and macrophages in liver, these results indicated that LPS induced sever ALI. As inflammatory response plays a vital role in the pathogenesis of LPS-induced ALI, we detected the occurrence of pyroptosis in liver by ribonucleic acid (RNA) sequencing. The results showed that pyroptosis was significantly promoted by LPS, as indicated by gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses, revealing the activation of pyroptosis, interleukin (IL)-1 production, IL-18 production, and inflammatory signaling pathways. Then, we explored the effect of SFN on LPS-induced ALI. The results showed that SFN obviously reduced LPS-induced plasma alanine aminotransferase and aspartate aminotransferase level, pathological injuries and TdT-mediated dUTP nick-end labeling (TUNEL) positive cells, indicating protective effect of SFN on ALI. Furthermore, SFN also showed robust effect on LPS-induced inflammatory response in liver, as reflected by suppressing the infiltration of neutrophils and macrophages, and downregulating mRNA levels of C-X-C motif chemokine ligand 9, IL-6, monocyte chemoattractant protein-1, and tumor necrosis factor-α in liver of LPS treated mice. Furthermore, SFN blocked hepatocyte pyroptosis, and suppressed plasma IL-1β and IL-18 levels of LPS treated mice. Mechanistically, SFN selectively activated nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling to mediate pyroptotic cell death. SFN also reversed the inhibited superoxide dismutase activity and induced malondialdehyde content in liver of LPS exposed mice.ConclusionSFN ameliorated liver injury and inflammation during LPS-induced ALI by suppressing hepatocyte pyroptosis via the activation of Nrf2/HO-1 signaling. This study provides new evidence for the potential treatment of ALI with SFN.